Rancangan Aplikasi Marketplace UMKM Ayam Kremes Sambal Embe Bali Di Kota Padang Menggunakan Aplikasi Blogger - Cantika Erina Putri; Yolanda Aprilia S; Irfan Efendi; Sularno; Novadilatri (CV. ITTC INDONESIA, 2024)
This study aims to facilitate and manage MSMEs in promoting and marketing the products they produce so that they are more widely accessible in the industry in utilizing social media as a means of digital marketing by Restoran Ayam Geprek to maintain business and attract consumer interest. Then the study provides an in-depth description of the management of social media by the restaurant. The case study method is used to explore the use of Marketplace. Data were collected through interviews, observations, and document studies, then analyzed descriptively. The results of the study indicate that there are obstacles in utilizing social media, such as lack of knowledge and skills, limited time and human resources, and lack of interesting strategies and content. Therefore, it is important for restaurants to overcome these problems in order to increase their presence on social media, interact with customers effectively, and implement a consistent and innovative digital marketing approach using the Blogger Application. Keywords: Social Media, Digital Marketing, and Blogger.